Entrepreneurial motivation, psychological capital, and business success of young entrepreneurs in the DRC - Ephrem, A.N.; Dontsop Nguezet, Paul M.; Charmant, I.K.; Murimbika, M.; Awotide, B.A.; Abdoulaye, Tahirou; Lydie, M.N.; Manyong, Victor (MDPI, 2021)
The proponents of the entrepreneurial motivation dichotomy have argued that opportunity-driven entrepreneurs are more likely to succeed and sustain in entrepreneurship, unlike people who start-up businesses out of necessity. However, disagreement still exists on why and under which conditions the former might outperform the latter. This research contributes to this debate by examining the mediation role of psychological capital in the relationship between entrepreneurial motivation and business success among youths. This study relied on a random sample of 295 young entrepreneurs surveyed from Bukavu in the Democratic Republic of the Congo (DRC). We applied partial least squares to analyze the hypothesized relationships. Evidence for the positive effect of opportunity-led motivation on psychological capital was found, but the findings did not support any direct effect of entrepreneurial motivation on business success. Instead, psychological capital positively and significantly mediated the relationship between entrepreneurial motivation and business success. This paper makes a distinctive new contribution to the understanding of the intriguing and controversial entrepreneurial motivation dichotomy—a business success relationship. To this end, we have found out that opportunity entrepreneurs have 3% more chance of succeeding in businesses compared to necessity entrepreneurs, because the former outperform the latter by 4% in the dimensions of psychological capital. This paper has new policy implications, as it reveals the great importance of psychological capital in promoting business success, thus reducing unemployment among youths, and offers tips from which psychological capital can be built or improved.